Early Life Exposure to the Great Chinese Famine (1959-1961) and the Health of Older Adults in China: A Meta-Analysis (2008-2023) - Chi Shen; Xi Chen (Global Labor Organization (GLO), 2024)
There is mounting evidence indicating that the aging process initiates during early life stages, with in utero the individual's environment playing a significant role. Consequently, it is crucial to comprehend the enduring effects of early life circumstances on health in old age. In this study, we conducted a meta-analysis to examine the effects of the Great Chinese Famine (1959-1961) on the health of older adults. We also explored potential mechanisms underlying these effects. The complex interplay between early life circumstances, multiple health-related sectors, and healthy aging necessitates a comprehensive life-course approach and strategic interventions to enhance public health in an aging society.
Keywords: I14; J14; J13; I18; 330; Meta-Analysis; Aging; Life Course Health; Famine; Early Life Circumstances